Influence of minimal extended firing on dimensional, optical, and mechanical properties of crystalized zirconia-reinforced lithium silicate glass ceramic. (April 2020) - Schweitzer, Florian; Spintzyk, Sebastian; Geis-Gerstorfer, Juergen; Huettig, Fabian
Abstract: This study should evaluate the influence of extended firing on the dimension, optical properties and flexural strength of a fully crystalized zirconia-reinforced lithium-silicate ceramic (ZLS) for single tooth restorations. Methods: 150 ZLS (Celtra Duo) and 30 lithium disilicate (LDS, IPS e.max CAD) specimens (17 × 4 × 1 mm) were milled in a standard device (Cerec MC XL). The ZLS specimens were distributed equally to five experimental groups (polished, standard firing [IFU], and three extended firings). LDS acted as a control group. The extended firings of ZLS addressed the first glaze firing (EF1) as well as the subsequent glaze firing (EF2) by a controlled overheating of +15 °C during the holding time. Color was measured with a digital spectrophotometer (Shadepilot), and dimensions with a digital calliper, before and after firing. A color change of ΔE ≥1.5 and a volume change of ±0.5% was regarded as clinical relevant. All specimens underwent a three-point-bending test to calculate flexural strength and Weibull statistics. Results: The color change after firing of ZLS (ΔE value; mean = 1.06; SD = 0.53) exceeded the perceptible threshold of ΔE ≥1.5 in 20% of IFU (mean = 1.18) and EF1+2 (mean = 0.95), 23% of EF1 (mean = 1.11), and 10% of EF2 (mean = 0.99) specimens with no statistical difference between the experimental groups. In 80% of IFU, 63% of EF2, 56% of EF1, and 33% of EF1+2 vol. change after firing exceeded ±0.5%. Characteristic Weibull strength σ0 and modulus m of polished ZLS specimen was affected by firing in IFU (σ0 = 314.35 MPa; m = 5.81), EF1 (σ0 = 324.68 MPa; m = 5.67), EF2 (σ0 = 326.4 MPa; m = 7.24), and EF1+2 (σ0 = 357.15 MPa, m = 3.69). LDS revealed σ0 = 405.7 MPa; m = 8.04, and polished ZLS σ0 = 219.3 MPa; m = 8.9 with statistical significant difference of the flexural strength between all fired ZLS experimental groups towards "as polished" as well as LDS. Conclusion: Firing of ZLS led to changes in dimensions, color, and Weibull modulus. Firing increases flexural strength, but minimal temperature extension also increases materials inhomogeneity and risk of failure. The findings call for further investigations towards firing behavior of ZLS and its clinical relevance for restorations. Graphical abstract: Image 1 Highlights: Minimal temperature extension is a prevalent practical risk when firing ceramics. Firing of ZLS led to changes in dimension, color, and flexural strength. Consecutive extended firing of ZLS increased the materials inhomogenity. minimal firing deviations in ZLS bear a potential risk for later clinical failure.